Intoxicant use in the prehistoric Caribbean with particular reference to spouted ceramic inhaling bowls. - Quetta Kaye (Papers from the Institute of Archaeology, 1999)
The New World is unusually rich in hallucinogenic plants (Schultes and Hofmann 1980: 22). Ethnological research has well documented the ritual use of these substances by the inhabitants of the South American tropical rainforests (Wassen 1965). While archaeological research has tended to concentrate on the great ancient American civilisations of the Incas, Aztecs and Maya, which also reveal ritual usage of mind altering substances (Furst and Coe 1977; Coe 1988: 222-235; Bruhns 1994: 73-74, 215-216, 391), no comparable study or research has been undertaken for the pre-Columbian inhabitants of the Caribbean islands.
Keywords: ceramics; inhaling bowls; drugs; intoxicants